Network Proteins of Human Sortilin1, Its Expression and Targetability Using Lycopene - Arun H. S. Kumar (Life, 2024)
Background: Sortilin1 (SORT1) is a ubiquitously expressed transporter involved in sorting or clearing proteins and is pathologically linked to tissue fibrosis and calcification. Targeting SORT1 may have potential clinical efficacy in controlling or reversing cardiovascular fibrosis and/or calcification. Hence, this study assessed the protein–protein network of human SORT1 and its targetability using known nutra-/pharmaceuticals. Material and methods: Network proteins of human SORT1 were identified using the String database, and the affinity of the protein–protein interaction of this network was analysed using Chimera software (Chimera-1.17.3-mac64). The tissue-specific expression profile of SORT1 was evaluated and assessed for enrichment in different cell types, including immune cells. A library of in-house small molecules and currently used therapeutics for cardiovascular diseases were screened using AutoDock Vina to assess the targetability of human SORT1. The concentration affinity (CA) ratio of the small molecules was estimated to assess the clinical feasibility of targeting SORT1. Results: IGF2R, NTRK2, GRN and GGA1 were identified as high-affinity interaction networks of SORT1. Of these high-affinity interactions, IGF2R and GRN can be considered relevant networks in regulating tissue fibrosis or the microcalcification process due to their influence on T-cell activation, inflammation, wound repair, and the tissue remodelling process. The tissue cell-type enrichment indicated major expression of SORT1 in adipocytes, specialised epithelial cells, monocytes, cardiomyocytes, and thyroid glandular cells. The binding pocket analysis of human SORT1 showed twelve potential drug interaction sites with varying binding scores (0.86 to 5.83) and probability of interaction (0.004 to 0.304). Five of the drug interaction sites were observed to be targetable at the therapeutically feasible concentration of the small molecules evaluated. Empagliflozin, sitagliptin and lycopene showed a superior affinity and CA ratio compared to established inhibitors of SORT1. Conclusion: IGF2R and GRN are relevant networks of SORT1, regulating tissue fibrosis or the microcalcification process. SORT1 can be targeted using currently approved small-molecule therapeutics (empagliflozin and sitagliptin) or widely used nutraceuticals (lycopene), which should be evaluated in a randomised clinical trial to assess their efficacy in reducing the cardiac/vascular microcalcification process.